The Effect of Pharmacy Installation Services, Service Quality, and Patient Satisfaction on Patient Loyalty at Global Medical Center Clinic Batam - Riris Liani; Farida Yuliaty; Vip Paramarta; Kosasih; Rukhiyat Syahidin (LP2M IAIN Palopo, 2026)
The quality of healthcare services, particularly in the Pharmacy Installation, plays a crucial role in shaping patient satisfaction and loyalty at primary healthcare facilities. The phenomenon observed at Global Medical Center Clinic Batam reveals several challenges, including relatively long pharmacy service waiting times, unfriendly staff attitudes, limited drug information and education, and inadequate supporting facilities. These conditions have the potential to reduce patient satisfaction and loyalty, making it necessary to conduct an empirical study to determine the extent to which pharmacy installation services, service quality, and patient satisfaction can influence patient loyalty. This study employed a quantitative approach with a survey method conducted on 110 patient respondents. Data analysis was performed using SPSS software through validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that pharmacy installation services significantly influence patient loyalty (β = 0.206, p = 0.026); service quality significantly influences patient loyalty (β = 0.273, p = 0.006); and patient satisfaction significantly influences patient loyalty (β = 0.078, p = 0.035). Simultaneously, all three variables explain 83.3% of the variance in patient loyalty (F = 9.869, p = 0.000). Clinic management is advised to implement continuous improvements in pharmacy service aspects, service quality standards, and patient experience to maintain competitiveness and the clinic's reputation.